How Are Researchers Evaluating the Effectiveness of Educational VR Applications and What Outcomes Are They Obtaining? A Systematic Literature Review - Vásquez‐Carbonell, Mauricio; Torres, Juan C. (Computer animation and virtual worlds, 2025)
ABSTRACT Virtual environments in education offer numerous benefits, as shown by the growing volume of scientific research. However, understanding the effectiveness of VR applications, and evaluating study outcomes is imperative. To explore this further, a Systematic Literature Review was conducted, revealing various methods for evaluating the effectiveness of VR applications; however, questionnaires emerged as the most used approach. Outcome analysis suggests that traditional teaching methods can be as effective as VR, though this technology shows potential in stimulating cognitive and motor skills, with positive results in motivation and engagement. Cognitive load generated by information in Virtual Environment and Cybersickness are common issues, and long‐term impact and information on VR software development remain almost underexplored. These findings highlight the need for rigorous validation of VR in education, particularly to establish its long‐term benefits and usability.